Integral Assessment of Intrheateral Blood Flow - a New Direction in Non-Invasive Diagnostics of Chronic Liver Diseases - S. G. Manasyan; S. Yu. Ermolov; A. G. Apresyan; T. V. Ermolova (SINAPS LLC, 2023)
Purpose of the study. To assess the sensitivity, specificity and diagnostic accuracy of the method for non-invasive differential diagnosis of liver diseases by polyhepatography.Materials and methods. A random sampling method examined 45 primary patients. Polygepatography was performed on all patients to detect disorders of intrahepatic microcirculation during primary contacting. Based on the detected changes in intrahepatic hemodynamics and based on the morphofunctional hemodynamic model, a conclusion was made about the violation of intrahepatic blood flow and an assumption was made about the etiology and stage of liver disease. Subsequently, the diagnosis of liver diseases was verified after a detailed study of clinical-laboratory, instrumental and morphological data generally accepted in hepatology. Puncture liver biopsy by the Mancini method was performed in 11.1 % of the subjects.Results. All subjects were divided into three groups based on the data obtained on impaired intrahepatic hemodynamics during polyhepatography (PHG). The group I consisted of patients with impaired venous inflow, the group II included patients with impaired arteriovenous inflow, and group III - with impaired venous outflow. The obtained polyhepatographic data were compared with the results of clinical-laboratory, instrumental and morphological data. The high sensitivity, sufficient specificity and accuracy of the polyhepatography method in the diagnosis of chronic liver diseases have been determined.Conclusion. The studies carried out indicate that PHG is a simple, accessible and not burdensome examination method for the patient, which makes it possible to assess the localization of intrahepatic blood flow disorders, and, with a certain degree of probability, to assume the etiological factor of the disease and the stage of the disease. Given the specificity of changes in liver hemodynamics, de pending on the etiological factor and stage of the disease, assessment of intrahepatic hemodynamics by polyhepatography can be recommended as a screening method for examining patients with liver diseases, which will shorten the diagnostic search time.